Recent progress on the phytotoxic effects of hydrochars and toxicity reduction approaches - Karatas, Okan; Khataee, Alireza; Kalderis, Dimitrios (Pergamon-Elsevier Science Ltd, 2022)
Hydrothermal carbonization of wet biomasses has been known to produce added-value materials for a wide range of applications. From catalyst substrates, to biofuels and soil amendments, hydrochars have distinct advantages to offer compared to conventional materials. With respect to the agricultural application of hydrochars, both positive and negative results have been reported. The presence of N, P and K in certain hydrochars is appealing and may contribute to the reduction of chemical fertilizer application. However, regardless of biomass, hydrothermal carbonization results in the production of phytotoxic organic compounds. Additionally, hydro chars from sewage sludge often contain heavy metal concentrations which exceed the regulatory limits set for agricultural use. This review critically discusses the phytotoxic aspects of hydrochar and provides an account of the substances commonly responsible for these. Furthermore, phytotoxicity reduction approaches are proposed and compared with each other, in view of field-scale applications.
Keywords: Hydrothermal carbonization; Hydrochar; Phytotoxicity; Ecotoxicity; Soil amendment; Toxicity reduction